2019
DOI: 10.1111/ane.13200
|View full text |Cite
|
Sign up to set email alerts
|

Negative predictors of shunt surgery outcome in normal pressure hydrocephalus

Abstract: Objectives:The prevalence of idiopathic normal pressure hydrocephalus (iNPH) and vascular comorbidity increases with age. It has not been clarified if high age and vascular disease are negative predictors of shunt surgery outcome in patients with iNPH.The aim of this study was to investigate the impact of high age and vascular comorbidity on outcome after shunt surgery in patients with iNPH.Methods: All 332 patients with iNPH who were treated with shunts between 2011 and 2015 at a single centre were consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…The iNPH patients derived from Uppsala University hospital, where 332 patients with suspected iNPH received shunts during 2011-2015, previously described [17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The iNPH patients derived from Uppsala University hospital, where 332 patients with suspected iNPH received shunts during 2011-2015, previously described [17].…”
Section: Methodsmentioning
confidence: 99%
“…However, the observation in the present study that the iNPH Radscale discriminates between definite iNPH and asymptomatic individuals does not tell whether the scale can be used to predict the outcome of surgery as well. The indication for surgery must be evaluated separately, taking age, comorbidity and other prognostic factors into consideration [17,25]. The iNPH Radscale can be used on CT or MR scans when iNPH is suspected by the clinicians, or in en passant finding of ventriculomegaly for example in CT scans after fall accidents.…”
Section: Plos Onementioning
confidence: 99%
“…The sensitivity of 52.2% for the gait domain means that the prediction of a postoperative positive outcome is slightly better than pure chance. Increased age has been reported as a negative factor for shunt surgery outcome (31,37) but it has also been reported that the age alone should not exclude patients from surgery (38,39). A careful evaluation of patients over 80 years of age is important and the low accuracy of CSF TT for these patients has to be taken into consideration when deciding to offer a shunt operation.…”
Section: Discussionmentioning
confidence: 99%
“…The gait and balance domains are evaluated before and after the CFS TT. The Hellström iNPH scale is a standardized method that has rarely been used as an outcome measure in the evaluation of the CSF TT (23,31).…”
Section: Introductionmentioning
confidence: 99%
“…As such, differential effects on each component of the iNPH clinical triad could not be assessed. Similarly, in such small cohorts, it was not possible to control for other factors associated with shunt responsiveness, such as age [11,55], duration of symptoms [11,[56][57][58], gait disturbance predominance over cognitive impairment [10,11,57,58], the presence of co-morbidities [55,59], and the structural imaging features of iNPH and AD.…”
Section: Weaknesses Of Included Studiesmentioning
confidence: 99%